Analisis Strategi Customer Relationship Management Untuk Mempertahankan Loyalitas Pelanggan UMKM (Studi Kasus Singgah Selalu & Rumah Kue Alifa) - Mella Amanda; Retno Febriani; Juan Reza; Zulfachmi Zulfachmi (Jurnal Bangkit Indonesia, 2022)
Micro, small and medium enterprises are a field of business that is very helpful in various aspects of the Indonesian economy. This research was conducted to analyze the customer relationship management strategy to maintain customer loyalty which is run by Singgah Always and Rumah Kue Alifa. The approach in this research is qualitative with case study method and uses interview, observation and documentation data collection techniques. The customer relationship management strategy implemented is in the form of identifying customers, listening to customer needs and providing services in meeting customer needs and creating customer relationship management programs in the form of member programs and discount events which can benefit customers. With this program, it is expected to maintain customer loyalty to the two UMKMs.